Analisis Hidrologi Model Soil Moisture Accounting Dengan Metode Kalibrasi Root Mean Square Error (Studi Kasus : DAS Rokan, AWLR Pasir Pangaraian) - David Imannuel Ketaren; Yohanna Lilis Handayani; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
One model of the transformation of rain into debit is the Hydrologic Engineering Center - Hydrologic Modeling System model or abbreviated as HEC-HMS, and one of the calculation methods is Soil Moisture Accounting. This model simulates the movement of water through and storing water in vegetation, at ground level, in soil profile, and in the groundwater layer. The purpose of this study was to calculate and analyze the resulting value of the Soil Moisture Accounting method with Root Mean Square Error calibration and for the Rokan Watershed with AWLR Pasir Pangaraian. This study uses rain data and discharge data with a data length of 10 years, from 2008-2017. This research took place in the Rokan AWLR Pasir Pangaraian watershed using the HEC-HMS program. Hydrological Modeling uses a calibration method which is the Root Mean Square Error (RMSE) method. Based on the nine calibration decisions, the value of Root Mean Square is best at approval I with a value of 99.10, while the value verification of Root Mean Square is best at reporting II with a value of 90.20425. Keywords: availability of water, HEC-HMS, Soil Moisture Accounting, RMSE